One Decade, 20 Percent Education Budget: How About Causality Between Education Success and Poverty? - Wijaya, Putu Yudy; suasih, Nyoman reni (Jurnal Ekonomi Kuantitatif Terapan, 2021)
In 2019, exactly one decade of the government expenditure on education in Indonesia (central and local government) was allocated 20 percent. The purpose of this study was to analyze the causality relationship between government budget on education, education success (proxied by the mean years of schooling), and poverty (proxied by the number of poor people) in Indonesia. The data analyzed is secondary data, to be precise panel data from 34 provinces in Indonesia over a period of five years (2015-2019). The analysis technique used is the Granger Causality Test. The results showed that the government budget on education had a significant effect on the mean years of schooling and had a causal relationship with poverty. Meanwhile, poverty has been shown to affect the mean years of schooling. Based on the results of this analysis, it is for the government to consistently prioritize the budget for the education sector because it is proven to have an impact on education success and poverty alleviation. In addition, the government also needs to pursue poverty alleviation programs such as subsidizing cash assistance for student in poverty.